TRADE AND GROWTH IN INDIA: AN ANALYSIS OF THE RELATIONSHIP AND ITS IMPLICATIONS - Irshad Ahmad Reshi; Dr T. Sudha (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This research paper examines the relationship between trade and economic growth in India. India is one of the fastest-growing economies in the world and has witnessed a significant increase in trade over the past few decades. The paper analyzes the impact of trade on growth in India, focusing on both the theoretical and empirical aspects. It also discusses the challenges faced by India in the context of international trade and the policies required to ensure sustainable economic growth. Trade and economic growth have been closely intertwined in India over the past few decades, with India emerging as a key player in the global economy. This abstract provides an overview of the relationship between trade and growth in India, highlighting key trends and factors that have influenced the country's economic development.